PENGARUH DOSIS SUBLETAL EKSTRAK SAMBILATA (ANDROGRAPHIS PANICULATA NEES) TERHADAP AKTIVITAS MUSUH ALAMI DAN KEPERIDIAN WERENG HIJAU, NEPHOTETTIX VIRESCENS DISTANT - I Nyoman Widiarta dan Dede Kusdiaman . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2008)
Effect of sublethal doses of sambilata extract to the fecundity and natural enemies activity of the green leafhopper, Nepothettix virescens Distant. Sambilata (Andrographis paniculata) is a tropical herb which has antifeeding property and could reduce rice tungro virus transmission by the rice green leafhopper (GLH), Nephotettix virescens. Series of test were conducted to clarify the effect of sublethal doses of sambilata to the fecundity and natural enemies activity of the GLH. The objective of the test was to know wether sublethal dose of sambilata could cause physiological or ecological resurgence. The results of test showed that foliar spraying of sambilata extract at concentration of 100 and 1000 ppm to rice seedlings reduced the GLH females’s fecundity. Spraying sambilata extract up to dose of 100 ppm on rice seedlings and GLH did not reduce Lycosa preying activity. Egg parasitoid activity was not affected by sambilata application on rice seedlings bore GLH eggs. Thus the probability of sublethal dose of sambilata to cause physiological or ecological resurgence was low.